PENDEKATAN KONSELING ISLAM DI RUMAH SAKIT DALAM MENINGKATKAN KESEJAHTERAAN PSIKOSPIRITUAL PASIEN : LITERATURE REVIEW TERHADAP PERAN KONSELOR DALAM LAYANAN KESEHATAN BERBASIS ISLAM - Putri Rahmadani; Lusia Juniarti; Fadila; Syamsul Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Patient health is a holistic condition that encompasses physical, psychological, social, and spiritual aspects. The Islamic counseling approach in hospitals is an important strategy for enhancing patients’ psychospiritual well-being, particularly among Muslim patients. This study aims to analyze the role of counselors in Islamic counseling services in hospitals through a literature review of 12 scientific articles published between 2020 and 2025. The results indicate that Islamic counseling is effective in reducing anxiety, enhancing inner peace, and strengthening patients’ spiritual coping mechanisms through approaches such as prayer, dhikr, and tawakal. Counselors serve as spiritual facilitators, motivators, emotional guides, and professionals in Islam-based healthcare services. The integration of Islamic counseling into the healthcare system has been proven to improve patients’ quality of life holistically.